2003
DOI: 10.1177/1077559503254140
|View full text |Cite
|
Sign up to set email alerts
|

The Court-Appointed Special Advocate (CASA) Program: Bringing Information to Child Abuse & Neglect Cases

Abstract: The Court-Appointed Special Advocate (CASA) Program has been rapidly expanding in its 25-year history, although there has been little sound, empirical data assessing its value. The present study compared 21 judicial hearings regarding children who had a CASA with 20 hearings for children who were on a waiting list for a CASA. Judges, CASAs, and guardians ad litem provided the data for the study. The findings indicated that CASA involvement improves the breadth and quality of information provided to the courts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Another survey of over 500 judges showed that the majority of judges use the input that CASA provides in their decision making, and find that CASA is useful and effective in monitoring cases and considering the best interests of children (ORS, 2005). This finding is echoed in other studies that have conducted survey research, with judges and other child welfare professionals reporting overall high satisfaction and regard for the performance of CASA volunteers in advocating for children (Berliner & Fitzgerald, 1998;Leung, 1996;Litzelfelner, 2008;Weisz & Thai, 2003).…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Another survey of over 500 judges showed that the majority of judges use the input that CASA provides in their decision making, and find that CASA is useful and effective in monitoring cases and considering the best interests of children (ORS, 2005). This finding is echoed in other studies that have conducted survey research, with judges and other child welfare professionals reporting overall high satisfaction and regard for the performance of CASA volunteers in advocating for children (Berliner & Fitzgerald, 1998;Leung, 1996;Litzelfelner, 2008;Weisz & Thai, 2003).…”
mentioning
confidence: 59%
“…In studies directly comparing the performance and activities of CASA volunteers and attorneys, researchers have concluded that CASA volunteers perform at least as well as paid attorneys in representing the best interests of children in court (Condelli, 1988;Duquette & Ramsay, 1986;Poertner & Press, 1990;Weisz & Thai, 2003;Youngclarke, Dyer Ramos, & Granger-Merkle, 2004). In the earliest study looking at the relative performance of volunteer advocates and attorneys, Duquette and Ramsey (1986) found that lay volunteers (similar to CASA) spent more time on cases than paid attorneys with no specialized child advocacy training, and that there were no significant differences between the lay volunteers and paid attorneys on a host of measures related to legal activities (such as court processing time, placement orders, visitation orders, treatment orders, pleas, ward of court orders, and dismissals).…”
mentioning
confidence: 99%
See 3 more Smart Citations